Complete 1H and 13C NMR structural assignments for five semi-synthetic eremantholides - Sass, Daiane C. [UNESP]; Ferreira, Alexsandro E.; Vieira, Gabrielle [UNESP]; Rezende, Ana Laura M.; Kovatch, Pedro Y.; Palaretti, Vinícius; Constantino, Mauricio G.; Heleno, Vladimir C.G. (Elsevier, 2021)
Five eremantholides were prepared from natural furanoheliangolides by reductions with Stryker's reagent, in previous works. We thus decided to perform a detailed and complete assignment of all 1H and 13C NMR data for those compounds. Through NMR experiments such as 1H NMR, 13C {1H} NMR, gCOSY, gHMQC, gHMBC, J-resolved, among others, it was achieved an unequivocal assignment of 1H and 13C NMR data for all studied substances, with measurement of all H/H homonuclear coupling constants and the clarification of all hydrogen signals multiplicities. Those data were not completely available yet in the literature.
Keywords: Eremantholides; Multiplicities clarifying; NMR data; Sesquiterpene lactones